Conical Diffraction and Composite Lieb Bosons in Photonic Lattices - Diebel, Falko (2017)
Pseudospin describes how waves are distributed between different “internal” degrees of freedom or microscopic states, such as polarizations, sublattices, or layers. Here, we experimentally demonstrate and explain wave dynamics in a photonic Lieb lattice, which hosts an integer pseudospin s=1 conical intersection. We study the most striking differences displayed by integer pseudospin states: pseudospin-dependent conical diffraction and the generation of higher charged optical vortices.